2005
DOI: 10.5194/angeo-23-1807-2005
|View full text |Cite
|
Sign up to set email alerts
|

HF doppler sounder measurements of the ionospheric signatures of small scale ULF waves

Abstract: Abstract. An HF Doppler sounder, DOPE (DOppler Pulsation Experiment) with three azimuthally-separated propagation paths is used to provide the first statistical examination of small scale-sized, high m waves where a direct measurement of the azimuthal wavenumber m, is made in the ionosphere. The study presents 27 events, predominantly in the post-noon sector. The majority of events are Pc4 waves with azimuthal m numbers ranging from −100 to −200, representing some of the smallest scale waves ever observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Subsequently Baddeley et al (2005b) were able to demonstrate a statistically significant relationship between such population inversions and ionospheric observations of high-m waves. Baddeley et al (2005a) additionally provided evidence that in the pre-noon sector the drift-bounce resonance mechanism was statistically more likely whereas in the post-noon sector both a drift or drift-bounce resonance interaction was statistically possible. The analysis of magnetospheric ion distribution functions was extended to a wider range of invariant latitudes by Wilson et al (2006).…”
Section: The Origin Of the Small-scale Ulf Wavesmentioning
confidence: 89%
“…Subsequently Baddeley et al (2005b) were able to demonstrate a statistically significant relationship between such population inversions and ionospheric observations of high-m waves. Baddeley et al (2005a) additionally provided evidence that in the pre-noon sector the drift-bounce resonance mechanism was statistically more likely whereas in the post-noon sector both a drift or drift-bounce resonance interaction was statistically possible. The analysis of magnetospheric ion distribution functions was extended to a wider range of invariant latitudes by Wilson et al (2006).…”
Section: The Origin Of the Small-scale Ulf Wavesmentioning
confidence: 89%
“…Chisham (1996) suggested that the second mechanism may provide an explanation for the rarity of Pgs and their occurrence during geomagnetically quiet times. Several studies reported simultaneous observations of the bump-on-tail ion distribution functions and the poloidal pulsations very similar or identical to Pgs (Hughes et al, 1979;Baddeley et al, 2005).…”
Section: Modeling and The Purpose Of This Papermentioning
confidence: 99%
“…One of them is the coincidence of the directions of the azimuthal phase velocity of the high-m pulsations and the proton drift velocity (Fenrich et al, 1995;Yeoman et al, 2000;Baddeley et al, 2005b;Glassmeier, 1980). Besides, both velocities depend on the radial coordinate almost in the same way (Allan et al, 1982(Allan et al, , 1983.…”
Section: Introductionmentioning
confidence: 99%